Interworking of a satellite system for mobile multimedia applications with the terrestrial networks. - Priscoli, F.D.
This paper deals with the interworking of a satellite system for mobile multimedia applications with the terrestrial environment. The concept of an ?overlying network? is introduced with the aim of giving a common approach for the interworking of the considered satellite system with the various terrestrial networks (B-ISDN, N-ISDN, TCP/IP). The paper particularizes the introduced concept to the case in which the considered satellite system is interfaced with the broadband ISDN (B-ISDN)
Keywords: ATM; B-ISDN.; N-ISDN.; TCP/IP.; Broadband ISDN; Interworking; Mobile multimedia applications; Overlying network; Personal mobile communication; Satellite system; Terrestrial networks